The Experiencing Self and the Remembering Self: Implications for Leisure Science. (2nd November 2017) - Zajchowski, Chris A. B.; Schwab, Keri A.; Dustin, Daniel L.
ABSTRACT: In this research reflection we question the way leisure experience is commonly understood and how leisure science is commonly conducted. Specifically, we focus on advances in multiple self-theory popularized by Daniel Kahneman in Thinking, Fast and Slow, an in-depth examination of human thought processes. After establishing Kahneman's foundational perspective, we apply his thinking to leisure experience and leisure science by reviewing recent scholarship focused on the "experiencing" and "remembering" selves (2000). We conclude the reflection by discussing the implications of Kahneman's thinking for the use of self-reports by leisure scientists, as well as call for greater congruence between the selves we seek to research and our selected research methods.